The biocompatibility of novel starch-based polymers and composites : in vitro studies - Marques, A. P. (2002)
Studies with biodegradable starch-based polymers have recently demonstrated that these materials have a range of properties, which make them suitable for use in several biomedical applications, ranging from bone plates and screws to drug delivery carriers and tissue engineering scaffolds. The aim of this study was to screen the cytotoxicity and evaluate starch-based polymers and composites as potential biomaterials. The biocompatibility of two different blends of corn-starch, starch/ethylene vinyl alcohol (SEVA-C) and starch/cellulose acetate (SCA) and their respective composites with hydroxyapatite (HA) was assessed by cytotoxicity and cell adhesion tests. The MTT assay was performed with the extracts of the materials in order to evaluate the short-term effect of the degradation products. The cell morphology of L929 mouse fibroblast cell line was also analysed after direct contact with polymers and composites for different time periods and the number of cells adhered to the surface of the polymers was determined by quantification of the cytosolic lactate dehydrogenase (LDH) activity. Both types of starch-based polymers exhibit a cytocompatibility that might allow for their use as biomaterials. SEVA-C blends were found to be the less cytotoxic for the tested cell line, although cells adhere better to SCA surface. The cytotoxicity test also revealed that SCA and SEVA-C composites have a similar response to the one obtained for SCA polymer. Scanning electron microscopy (SEM) analysis showed that cells were much more spread on the SCA polymer and LDH measurements showed a higher number of cells on this surface.